Effect of Different Levels of Paclobutrazol on the Yield of Asha and Farmers' Variety of Peanut - Mary Grace Gatan; Virgilio Gonzales (Philippine Association of Institutions for Research, Inc., 2015)
Peanut (Arachis hypogaea)  is commonly grown during the dry season and most farmers used the native variety. Growth retardants such as paclobutrazol (PBZ) was found to increase yield of some important crops. A study was conducted to determine the effect of different levels of paclobutrazol on the peanut yield of Asha and Farmers' variety during the wet season. The experimental area was laid out using Randomized Complete Block Design (RCBD) factorial. Treatments were replicated thrice. Data were analyzed by Analysis of Variance (ANOVA) and the Honest Significant Difference (HSD) test was used to compare treatment means. The increasing level of PBZ increased the number of pods of Asha by 29.97% while the most number of seeds was obtained from farmers' variety. Applied PBZ Asha at 150mg/L recorded the highest shelling percentage that is 16.19% higher when compared to the untreated. Paclobutrazol application significantly increased seed yield of Asha and farmers' variety by 43.34% and 20.86% at 150mg/L and 75mg/L, respectively. The increase in yield was due to the observed reduction in plant height and stem growth which possibly enhanced assimilate partitioning to pods. Asha applied with PBZ at 150mg/L obtained the highest seed yield of 4.2 tons/ha.